Method for testing creep crack growth rate of high-temperature long-time brittle material

By connecting multiple samples in series and applying loads in the creep testing machine, the existing test method has been solved the problem of complexity and limited accuracy of the existing test method, and the accurate test of the creep expansion rate of crispy material creep and long -term crispy material is achieved.

CN119354723APending Publication Date: 2025-01-24SHANGHAI ELECTRIC POWER GENERATION EQUIPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310910669.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing high-temperature long-term brittle materials have complex operation and limited accuracy, making it difficult to accurately measure the crack propagation rate, resulting in the underestimation of the material's resistance.

Method used

By connecting multiple specimens with the same nominal size in series, pre-cracks of different lengths are preformed, and loads are applied in a creep testing machine. The failure time and crack growth length of the specimens are recorded, and the crack growth rate and crack tip are calculated and plotted. For the corresponding curve of the initial stress intensity factor, perform function fitting to obtain the fitting parameters.

Benefits of technology

This method simplifies the testing process, avoids the use of high-cost equipment, and improves the accuracy of the test results. It is suitable for testing the creep crack growth rate of high-temperature and long-term brittle materials under working conditions where it is difficult to measure the crack length in real time. a reliable method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119354723A_ABST
    Figure CN119354723A_ABST
Patent Text Reader

Abstract

The invention provides a method for testing the creep crack growth rate of a high-temperature long-time brittle material, which comprises the following steps: processing a target material into a plurality of samples with the same nominal size, respectively prefabricating pre-cracks with different lengths on the N samples, with the length of the pre-cracks being a0i; connecting N samples in series to form a sample group, and assembling the sample group into a creep testing machine; calculating a crack tip initial stress intensity factor and failure fracture toughness corresponding to the sample under the same load; and drawing a corresponding curve of the crack growth rate and the initial stress intensity factor of the crack tip, and performing function fitting to obtain fitting parameters. The method has the beneficial effects that a plurality of samples are connected in series, and high-cost crack length real-time measuring equipment and loading linear displacement real-time measuring equipment are not required, so that the whole test process is simple, the physical significance is clear, and the test result is accurate; the method is suitable for testing the creep crack growth rate of the high-temperature long-time brittle material under the working condition that the crack length is difficult to test in real time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of high temperature mechanical testing, and in particular to a method for testing the creep crack growth rate of a high temperature and long-term brittle material. Background Art

[0002] For most metal materials, viscoplastic creep deformation related to temperature and time will occur under high temperature conditions, while for some high-temperature alloys, such as cobalt-based or cobalt-nickel-based alloys, they are still linear elastic and low-toughness under high temperature and long-term static load conditions, showing that the plastic deformation and creep deformation account for a small proportion, and crack propagation has the characteristics of rapid instability. Since the crack tip is little affected by creep deformation, the linear elastic stress intensity factor K can still be used to characterize the crack control parameter.

[0003] At present, the creep crack growth rate test is carried out in accordance with the American standard "ASTM E1457 Measurement of Creep Crack Growth Times in Metals". The test method is to prepare a group of specimens with the same nominal size and crack length, and apply different loads to obtain different creep crack growth rates. Since the crack growth length and loading line displacement are required to be measured in real time during the test, it is necessary to equip the crack length real-time test equipment and loading line displacement extensometer respectively. The commonly used crack monitoring method is DC or AC potential method, which is not only complicated to operate, but also has limited accuracy. This is because the crack of high-temperature and long-term brittle materials has a very small expansion before cracking, and is almost static for a long time. The crack size is difficult to measure. Once the crack starts, it will quickly expand to instability. The crack length measured by the current equipment is often the instability expansion part, resulting in a larger crack growth rate, which greatly underestimates the resistance of the material to creep crack growth. Summary of the invention

[0004] In view of the above-mentioned defects, the purpose of the present invention is to provide a method for testing the creep crack growth rate of brittle materials at high temperature and for a long time to solve the above-mentioned problems.

[0005] The present invention provides a method for testing the creep crack growth rate of a high-temperature, long-term brittle material, comprising the following steps:

[0006] The target material is processed into N specimens with the same nominal size, each specimen is numbered i, i=1, 2...N; pre-cracks of different lengths are pre-fabricated on the N specimens, and the length of the pre-cracks is a 1i ;

[0007] Connect the N specimens in series to form a specimen group, and place the specimen group into a creep testing machine;

[0008] Heat and keep the sample group warm, apply a load F and keep the load until a sample fails, and record the failure time of the sample as t i , stop the temperature and unload, and remove the failed specimen after it drops to room temperature;

[0009] Repeat the operation until all specimens fail;

[0010] Measure the true pre-crack length a of the specimen 0i and the final crack length a fi , and obtain the crack extension length △a of the sample i =a fi -a 0i ;

[0011] The crack growth rate of the sample is obtained according to the crack growth length and the failure time.

[0012] Calculate the initial stress intensity factor at the crack tip and the failure fracture toughness of the specimen under the same load;

[0013] The corresponding curves of the crack growth rate and the initial stress intensity factor at the crack tip are drawn and function fitting is performed to obtain fitting parameters.

[0014] Preferably, the number N of samples is greater than or equal to 5.

[0015] Preferably, the relationship between the pre-crack lengths of the N samples is: 11 <…… 1N ;

[0016] Crack growth rate of sample No. N

[0017] Crack growth rate of specimens with specimen number less than N

[0018] Preferably, the specimen is a step-type compact tensile specimen.

[0019] Preferably, the N specimens are connected in series through a clamp; the clamp comprises two U-shaped parts, a plurality of pins and a plurality of connecting parts, the U-shaped part is provided with a threaded connecting rod, the threaded connecting rod is threadedly connected to the tensile end of the creep testing machine, and the specimen is detachably connected to the U-shaped part and the connecting part through the pin.

[0020] Preferably, thermocouples are bundled at the upper, middle and lower parts of the sample group for temperature measurement and temperature control, and the temperature control accuracy is ±2°C. Preferably, the stress intensity factor K is calculated by formula (1):

[0021]

[0022] ​Where: F is the applied load, B is the sample thickness, B N is the net thickness of the specimen, W is the width of the specimen, a is the crack length, is a correction function related only to a and W;

[0023] The actual pre-crack length a 0i Substituting into formula (1), we can obtain the initial stress intensity factor K at the crack tip: 0i ;

[0024] The final crack length a fi Substituting into formula (1), we can obtain the failure fracture toughness K fi .

[0025] Preferably, Calculated by formula (2):

[0026]

[0027] Preferably, the crack growth rate is plotted and the initial stress intensity factor K at the crack tip 0i The corresponding curve of is fitted according to formula (3).

[0028]

[0029] Get the fitting coefficient A and fitting index m.

[0030] The benefit of the present invention lies in that, by connecting multiple specimens in series, there is no need to equip high-cost real-time crack length measurement equipment and loading line displacement real-time measurement equipment. The entire test process is simple, the physical meaning is clear, and the test results are accurate. It is suitable for creep crack growth rate testing of high-temperature and long-duration brittle materials under working conditions where it is difficult to test the crack length in real time. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is the front view and side view of the specimen in the initial state;

[0032] Figure 2 It is the front view and side view of the specimen group;

[0033] Figure 3 Schematic diagram of the relationship between crack extension length and time in an embodiment of the present invention;

[0034] Figure 4 It is a corresponding curve of the creep crack growth rate and the initial stress intensity factor at the crack tip obtained by the test method of the embodiment of the present invention.

[0035] Component number description:

[0036] 1. Sample

[0037] 11 Pin hole

[0038] 2 Threaded connecting rod

[0039] 3. Connection

[0040] 4 U-shaped part

[0041] 5 Pin DETAILED DESCRIPTION

[0042] The specific embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings. These embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0043] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0044] Furthermore, in the description of the present invention, unless otherwise specified, “plurality” means two or more.

[0045] The present invention provides a method for testing the creep crack growth rate of a high-temperature, long-term brittle material, comprising the following steps:

[0046] S1, such as Figure 1 As shown, the target material is processed into N specimens with the same nominal size, and the specimen number of each specimen is i, i=1, 2...N. N is preferably greater than or equal to 5. Specifically, the specimen is a step-type compact tensile specimen (CT specimen), such as Figure 1 As shown, two pin holes 11 are symmetrically opened about the central axis of the sample 1, and the pin holes 11 are used for the pin shaft to pass through and perform subsequent connection and stretching operations. The sample 1 has a sample thickness of B and a width of W.

[0047] S2. At room temperature, clamp a COD gauge on each specimen and install it on a fatigue testing machine to prefabricate fatigue cracks. The length of the pre-crack on the specimen is recorded as a 1i , the relationship between the pre-crack lengths of N specimens is: a 11 12 … 1N , that is, the larger the sample number, the larger the pre-crack length.

[0048] S3, connect N samples in series to form a sample group and load it into the creep testing machine. Figure 2 ​​As shown, the fixture includes two U-shaped parts 4, a plurality of pins 5 and a plurality of connecting parts 3. Among them, a threaded connecting rod 2 is provided on the U-shaped part 4, and the threaded connecting rod 2 is threadedly connected to the tensile end of the creep tester. Specifically, the connecting part 3 is in the form of a sheet, and two through holes are formed thereon, and a through hole is formed on each of the two clamping arms of the U-shaped part 4, and the pin hole 11 of the sample 1 is detachably connected to the through holes on the U-shaped part 4 and the connecting part 3 through the pin 5.

[0049] The installation method of the sample group includes: the upper end of the first sample is installed between the two clamping arms of the U-shaped part located at the upper end through the first pin shaft, the lower end of the first sample is installed at the upper end of the first connecting part through the second pin shaft, and the lower end of the first connecting part is connected to the upper end of the second sample through the third pin shaft, and the installation is carried out in sequence until the lower end of the last sample is installed between the two clamping arms of the U-shaped part located at the lower end through the last pin shaft, so as to realize the series connection of N samples 1.

[0050] After the series connection is completed, the samples are assembled into the creep tester so that all samples are located in the soaking zone of the high-temperature furnace. Then, thermocouples are tied to the upper, middle and lower parts of the sample group for temperature measurement and temperature control. The temperature control accuracy is ±2.

[0051] S4. Control the high temperature furnace to heat up to the preset temperature T. After keeping the temperature for 0.5 to 1 hour, apply the load F to the sample group. Keep the temperature and load until the first sample fails. Generally, the sample with the largest pre-crack length fails first. Record the failure time t of the sample. i , then stop the temperature and unload, wait for the furnace temperature to drop to room temperature before removing the failed sample.

[0052] S5. Repeat the above step S4 until all samples fail.

[0053] S6. Pull off the incompletely broken failed specimen and use an optical measuring device to measure the true pre-crack length a at the failed test fracture. 0i and the final crack length a fi , and obtain the crack extension length △a of the sample i =a fi -a 0i This is because in step S1, the pre-crack length a obtained by measuring the surface of the sample 1i and the actual pre-crack length a 0i There is an error between them. To ensure the accuracy of the calculation results, a fi -a 0i To replace a fi -a 1i Calculate the crack extension length.

[0054] S7. Calculate the crack growth rate of the specimen The specific algorithm is as follows:

[0055] Crack growth rate of the specimen with the largest pre-crack length and specimen number N

[0056] Crack growth rate of specimens with specimen number less than N

[0057] S8, stress intensity factor K is calculated by formula (1):

[0058]

[0059] Where: F is the applied load, B is the sample thickness, B N is the net thickness of the specimen, W is the width of the specimen, a is the crack length, is a correction function related only to a and W;

[0060] The actual pre-crack length a 0i Substituting into formula (1), we can obtain the initial stress intensity factor K at the crack tip: 0i ;

[0061] The final crack length a fi Substituting into formula (1), we can obtain the failure fracture toughness K fi ;

[0062] Calculated by formula (2):

[0063]

[0064] S9. Plotting the crack growth rate and the initial stress intensity factor K at the crack tip 0i The corresponding curve is fitted according to formula (3) to obtain the fitting coefficient A and fitting index m.

[0065]

[0066] The following is a specific embodiment of the present invention:

[0067] In this embodiment, the material to be tested is Co-Ni alloy, and the test temperature is 600°C.

[0068] S1, such as Figure 1 As shown, the target material is processed into 5 specimens 1 with the same nominal size, the specimen numbers are 1-5#, and the specimen thickness B of each specimen 1 is 10 mm and the specimen width W is 20 mm.

[0069] S2. Clamp the COD gauge on the five specimens respectively and install them on the fatigue testing machine to prepare pre-cracks of different lengths. The pre-crack lengths are a 11 =7.5mm, a 12=8.5mm, a 13 =9.0mm, a 14 =9.5mm, a 15 =10.0mm.

[0070] S3. Connect 5 samples in series into a sample group and install them in the creep testing machine. Make all the samples in series be located in the soaking zone of the high-temperature furnace. Bind thermocouples at the upper, middle and lower positions of the sample group for temperature measurement and temperature control. The temperature control accuracy is ±2°C.

[0071] S4. Control the high temperature furnace to heat up to 600℃. After keeping the temperature for half an hour, apply a load of F=2200N to the sample group. Keep the temperature and load until the first sample fails, that is, the 5# sample with the largest pre-crack length fails first. Record the holding time as t5 according to the sample number. Operate the testing machine and the high temperature furnace to unload and cool down. After the furnace temperature drops to room temperature, remove the failed 5# sample.

[0072] S5. Repeat the above step S4 until all samples fail.

[0073] S6. Pull off the incompletely broken failed specimen and use an optical measuring device to measure the true pre-crack length a at the failed test fracture. 0i and the final crack length a fi , and obtain the crack extension length △a of the sample i =a fi -a 0i .

[0074] S7. For brittle materials, the crack lengths of specimens with different pre-crack lengths are basically the same when they fail under the same load, that is, they have the same theoretical failure fracture toughness K. f And the relationship curve between the theoretical crack extension length and time Δa-t. Figure 3 As shown in the figure, the expansion curves of the specimens with different pre-crack lengths are taken as different stages of the Δa-t curve. For the 5# specimen with the largest pre-crack length, the crack growth rate calculation formula is: For 1-4# specimens, the crack growth rate calculation formula is:

[0075] S8, stress intensity factor K is calculated by formula (1):

[0076]

[0077] Where: F is the applied load, B is the sample thickness, B N is the net thickness of the specimen, W is the width of the specimen, a is the crack length, is a correction function related only to a and W;

[0078] The actual pre-crack length a0i Substituting into formula (1), we can obtain the initial stress intensity factor K at the crack tip: 0i ,Right now:

[0079]

[0080] The final crack length a fi Substituting into formula (1), we can obtain the failure fracture toughness K fi ,Right now:

[0081]

[0082] Calculated by formula (2):

[0083]

[0084] The actual pre-crack length a 0i Substituting into formula (2), we can obtain:

[0085]

[0086] The final crack length a fi Substituting into formula (2), we can obtain:

[0087]

[0088] S9, such as Figure 4 As shown, the crack growth rate is plotted and the initial stress intensity factor K at the crack tip 0i The corresponding curve of is fitted according to formula (3):

[0089]

[0090] The fitting coefficient A=3.6049E-13 and the fitting index m=8.746 were obtained.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and substitutions can be made without departing from the technical principles of the present invention. These improvements and substitutions should also be regarded as the scope of protection of the present invention.

Claims

1. A method for testing the creep crack growth rate of high temperature and long time brittle materials, characterized in that: The following steps are involved: The target material is processed into N specimens with the same nominal size, each specimen having a specimen number i, i=1, 2, ... N; pre-cracks of different lengths are pre-fabricated on the N specimens, and the pre-crack length is a 1i ; Connect the N specimens in series to form a specimen group, and place the specimen group into a creep testing machine; Heat and keep the sample group warm, apply a load F and keep the load until a sample fails, and record the failure time of the sample as t i , stop the temperature and unload, and remove the failed specimen after it drops to room temperature; Repeat the operation until all specimens fail; Measure the true pre-crack length a of the specimen 0i and the final crack length a fi , and obtain the crack extension length △a of the sample i =a fi -a 0i ; The crack growth rate of the sample is obtained according to the crack growth length and the failure time. Calculate the initial stress intensity factor at the crack tip and the failure fracture toughness of the specimen under the same load; The corresponding curves of the crack growth rate and the initial stress intensity factor at the crack tip are drawn and function fitting is performed to obtain fitting parameters.

2. The testing method according to claim 1, characterized in that: The number N of samples is greater than or equal to 5.

3. The testing method according to claim 1, characterized in that: The relationship between the pre-crack lengths of the N samples is: 11 <…… 1N ;​ Crack growth rate of sample No. N Crack growth rate of specimens with specimen number less than N 4. The testing method according to claim 1, characterized in that: The specimen is a step-type compact tensile specimen.

5. The testing method according to claim 1, characterized in that: The N specimens are connected in series through a fixture; the fixture includes two U-shaped parts, multiple pins and multiple connecting parts, the U-shaped part is provided with a threaded connecting rod, the threaded connecting rod is threadedly connected to the tensile end of the creep testing machine, and the specimen is detachably connected to the U-shaped part and the connecting part through the pin.

6. The testing method according to claim 1, characterized in that: Thermocouples are respectively bundled at the upper, middle and lower parts of the sample group for temperature measurement and temperature control, and the temperature control accuracy is ±2°C.

7. The testing method according to claim 1, characterized in that: The stress intensity factor K is calculated by formula (1): Where: F is the applied load, B is the sample thickness, B N is the net thickness of the specimen, W is the width of the specimen, a is the crack length, is a correction function related only to a and W; The actual pre-crack length a 0i Substituting into formula (1), we can obtain the initial stress intensity factor K at the crack tip: 0i ; The final crack length a fi Substituting into formula (1), we can obtain the failure fracture toughness K fi .

8. The testing method according to claim 7, characterized in that: Calculated by formula (2):

9. The testing method according to claim 1, characterized in that: Plotting the crack growth rate and the initial stress intensity factor K at the crack tip 0i The corresponding curve of is fitted according to formula (3). Get the fitting coefficient A and fitting index m.